1987
DOI: 10.1111/j.1471-4159.1987.tb00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensinogen in Cerebrospinal Fluid Corresponds Chromatographically to the γ‐Form of Plasma Angiotensinogen

Abstract: Angiotensinogen (Aogen) (CA 11002-13-14), the prohormone of the neuro- and vasoactive peptide angiotensin II (Ang II) (CA 11128-99-7), is found in dog brain as well as in dog plasma. At 2-4 micrograms/ml CSF, Aogen comprises 1-2% of the total protein in dog CSF. Immunopurified CSF and plasma Aogen were compared by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and anion-exchange HPLC. Two major (alpha- and beta-) forms and one minor (gamma-) form of Aogen were observed in dog plasma. The majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…In dog brain, ϳ95% of recovered angiotensinogen has been reported to be extracellular (466), and Thomas et al (709) have demonstrated the distribution of angiotensinogen in the rat brain by immunocytochemistry. This is supported by findings that the cerebrospinal fluid of dog and rat contains considerable amounts of angiotensinogen (455,609).…”
Section: Central Nervous Systemsupporting
confidence: 58%
“…In dog brain, ϳ95% of recovered angiotensinogen has been reported to be extracellular (466), and Thomas et al (709) have demonstrated the distribution of angiotensinogen in the rat brain by immunocytochemistry. This is supported by findings that the cerebrospinal fluid of dog and rat contains considerable amounts of angiotensinogen (455,609).…”
Section: Central Nervous Systemsupporting
confidence: 58%